Global longitudinal strain is superior to ejection fraction for long‐term follow‐up after allogeneic hematopoietic stem cell transplantation. Issue 1 (7th November 2022) - Watanabe, Marika; Yakushijin, Kimikazu; Tanaka, Hidekazu; Chijiki, Ruri; Saeki, Miki; Hirakawa, Yuri; Takakura, Hidetomo; Usui, Yutaro; Ichikawa, Hiroya; Sakai, Rina; Matsumoto, Sakuya; Nagao, Shigeki; et al.
Abstract: Global longitudinal strain (GLS), a new cardiac parameter measured by the speckle‐tracking method, is reportedly more sensitive than ejection fraction (EF) in detecting slight cardiac dysfunction in heart failure patients. We validated the utility of GLS in allogeneic hematopoietic stem cell transplantation (HSCT) patients during a long‐term follow‐up. Medical records of patients who underwent allogeneic HSCT between 2013 and 2020 were reviewed retrospectively. We evaluated the last echocardiography performed before transplantation and those performed annually during the 5 years after transplantation. We also investigated newly diagnosed cardiac events, which developed after HSCT. Among 85 patients, 22 used cardioprotective drugs. The median follow‐up duration in surviving patients was 54.1 months (range, 2.9–92.6 months). GLS significantly decreased year by year, and patients taking cardioprotective agents tended to have a better GLS at 5 years than at 3 years, while EF did not change. Fifteen patients developed newly diagnosed cardiac events. Multivariate analysis revealed that low GLS and high serum ferritin levels at baseline were independently associated with the development of cardiac events. Therefore, we need a continuous follow‐up of cardiac function by GLS and prescription of cardioprotective drugs might be considered for HSCT patients with low GLS. Further research is warranted.